Need analysis of English for Specific Purposes (ESP) in Psychology: Identifying linguistics demands for academic and professional success - Benny Dele Bintang Ananta; Muhammad Firza Thoriq Sholahuddin; Dede Akmal Khotib; Rafika Rabba Farah (English Learning Innovation, 2025)
ESP or English for Specific Purposes is an instructional approach centered on addressing learners' specific goals and requirements. The ESP approach is particularly suited for students in Indonesia who are learning English, especially those studying in institutions where English is not the primary language. This study seeks to explore the needs of students who are currently registered in the ESP program at the University of Muhammadiyah Malang, Especially in Psychology faculties. A mixed-methods approach was employed, involving a sample of sixty-four participants (N=64). Data was collected through an online survey using closed-ended questionnaires for quantitative insights, and qualitative data was gathered through Semi-structured Interviews to explore learners' perceived needs. Data analysis using IBM SPSS 25 software revealed the importance of integrating effective language strategies into ESP courses to enhance students' communication skills with lecturers, peers, professionals, and clients. The findings emphasize the need for authentic activities and real-world scenarios to develop proficiency in speaking, listening, reading, and writing within the psychology context. Students highlighted the significance of engaging in meaningful interactions, attending conferences and presentations, reading specialized materials, and practicing academic writing tasks. However, the study has limitations, including relying on student perspectives and self-reported data. Further research is needed to validate the findings and consider the long-term impact of implementing the proposed changes to the ESP program. This study underscores the relevance of ESP methodologies in tailoring English education to the specific needs of Indonesian psychology students, contributing to their language development and preparedness for academic and professional success